Evaluasi Program Madrasah Ibtidaiyah Swasta dalam Meningkatkan Mutu Lulusan - Ahmad Gawdy Prananosa; Marianita Marianita; M. Rusni Eka Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the private madrasah ibtidaiyah program in improving the quality of graduates. This study uses a qualitative approach with phenomenological methods. This research was conducted in Madrasah Ibtidaiyah Assidiq Giriyoso, Jayaloka District, Musi Rawas Regency. The research subjects consisted of the Principal, Board of Teachers, Chairperson of the Foundation, Students. Data collection techniques consist of observation, interviews and documentation. While the data analysis technique according to Miles & Huberman is interactive model analysis. The results of the study, evaluation of the madrasa program is the most important thing in the success of madrasas in carrying out their programs, madrasas have carried out evaluation activities, so that obstacles and obstacles were identified, such as facility support and student readiness in participating in the tahfiz program, so that this can be a problem in the successful implementation of the madrasa program. However, this matter has been followed up to the head of the madrasah, so that it becomes a consideration for improvements to be made, so that in the future these obstacles and obstacles do not occur again. In conclusion, Madrasahs have carried out evaluation activities, so that obstacles and obstacles were identified, such as facility support and student readiness in participating in the tahfiz program, so that this can be a problem in the successful implementation of the madrasa program, but this has been followed up to the madrasa principal. Keywords: Evaluation, Program, Madrasah, Private